2023
DOI: 10.3389/fpls.2022.1053780
|View full text |Cite
|
Sign up to set email alerts
|

Low red to far-red light ratio promotes salt tolerance by improving leaf photosynthetic capacity in cucumber

Abstract: Soil salinity severely inhibits leaf photosynthesis and limits agricultural production. Red to far-red light ratio (R/FR) affects leaf photosynthesis under salt stress, however, its regulation mechanism is still largely unknown. This study investigated the effects of different R/FR on plant growth, gas exchange parameters, photosynthetic electron transport, Calvin cycle and key gene expression under salt stress. Cucumber seedlings were exposed to four treatments including 0 mM NaCl and R/FR=7 (L7, control), 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…It is important to note that earlier studies have underlined the importance of a low red to far-red (R/FR) ratio in governing plant growth. This not only stimulates an enlargement of the cell wall, leading to an increase in leaf area, but also improves leaf photosynthetic capacity, dry matter accumulation, and overall plant growth [46][47][48]. Our research affirms these findings, as it revealed an increase in leaf area and a reduction in leaf thickness under blue net, suggesting that these are adaptive responses for shaded leaves to maximize light transmission to the chloroplasts.…”
Section: Discussionsupporting
confidence: 84%
“…It is important to note that earlier studies have underlined the importance of a low red to far-red (R/FR) ratio in governing plant growth. This not only stimulates an enlargement of the cell wall, leading to an increase in leaf area, but also improves leaf photosynthetic capacity, dry matter accumulation, and overall plant growth [46][47][48]. Our research affirms these findings, as it revealed an increase in leaf area and a reduction in leaf thickness under blue net, suggesting that these are adaptive responses for shaded leaves to maximize light transmission to the chloroplasts.…”
Section: Discussionsupporting
confidence: 84%
“…Carbohydrate is a key indicator of fruit sweetness and is also related to fruit quality, such as firmness and volatile aroma [33]. Numerous studies proved that under salt stress, low R/FR significantly promoted leaf photosynthesis and carbohydrate accumulation in cucumber plants [17]. Consistent with this, our study illustrated that low R/FR significantly increased TSS and soluble sugar contents in tomato fruit under salt stress (Na+L vs. Na, Figure 5).…”
Section: Discussionsupporting
confidence: 83%
“…Wang et al [16] suggested that low R/FR benefited the increase in salt tolerance in tomato plants mainly through increasing SOD, POD and CAT contents and decreasing H 2 O 2 contents. Miao et al [17] found that low R/FR improved cucumber photosynthetic efficiency through enhancing the photosynthetic electron transfer rate and Calvin cycle, effectively alleviating the negative regulations of salt stress. Hayes et al [18] indicated that under low R/FR irradiation, PIFs up-regulated the expression of the BSK5 gene and induced auxin signaling, finally accelerating hypocotyl elongation in salt-stressed Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting the ratio of R/FR has also been shown to impact photosynthetic efficiency and flowering responses in both short-day and long-day plants, providing a means to control plant morphology architecture. The response occurs at both the plant level and the molecular level, with adjustments in photosynthetic electron transport and the path of light energy . Exposure to low ratios of R/FR was also found to improve the salinity tolerance in tomato seedlings and cucumber. , …”
Section: Introductionmentioning
confidence: 99%
“…4 Exposure to low ratios of R/FR was also found to improve the salinity tolerance in tomato seedlings and cucumber. 14,15 Different ratios of R/FR can have an impact on the bioactive compounds in green leafy vegetables that are beneficial to humans, such as carotenoids, anthocyanins, flavonoids, antioxidants, and minerals, 5,16,17 but the effects on these nutritional constituents have been explored finitely and conflictingly. For example, an increasing FR intensity was reported to improve the bioactive compounds in lettuce.…”
Section: Introductionmentioning
confidence: 99%